Production of Bio-Oil from Municipal Solid Waste by Pyrolysis (Bangladesh Journal of Scientific and Industrial Research, 2010)
Municipal solid waste was pyrolyzed in a tubular reactor under vacuum. The effect of pyrolysis temperature and holding time on the product yields were investigated and the optimum conditions for pyrolysis were settled. The products of the pyrolysis were liquid pyrolytic oil, solid char and gaseous mixture. The pyro-oil was collected in a series of ice-cooled collectors. The uncondensed gas was blown off and the solid char was collected from the pyrolyser as a residue. The pyro-oil was then analyzed for fuel properties and chemical composition. The experimental result of gas chromatography & mass spectroscopy showed that the pyro-oil derived from the pyrolysis of municipal solid waste contained considerable amounts of carbonyl groups and/or oxygen content, resulting in low pH and low heating value. Key words: Municipal solid waste; Pyrolysis; Yield; Pyrolytic oil; Fuel properties; Chemical composition DOI: 10.3329/bjsir.v45i2.5703Bangladesh J. Sci. Ind. Res. 45(2), 91-94, 2010